Structural variation of centromeric endogenous retroviruses in human populations and their impact on cutaneous T-cell lymphoma, Sezary syndrome, and HIV infection - DİRESKENELİ, RAFİ HANER (BMC, 2019)
BackgroundHuman Endogenous Retroviruses type K HML-2 (HK2) are integrated into 117 or more areas of human chromosomal arms while two newly discovered HK2 proviruses, K111 and K222, spread extensively in pericentromeric regions, are the first retroviruses discovered in these areas of our genome.MethodsWe use PCR and sequencing analysis to characterize pericentromeric K111 proviruses in DNA from individuals of diverse ethnicities and patients with different diseases.ResultsWe found that the 5 LTR-gag region of K111 proviruses is missing in certain individuals, creating pericentromeric instability. K111 deletion (-/- K111) is seen in about 15% of Caucasian, Asian, and Middle Eastern populations; it is missing in 2.36% of African individuals, suggesting that the -/- K111 genotype originated out of Africa. As we identified the -/-K111 genotype in Cutaneous T-cell lymphoma (CTCL) cell lines, we studied whether the -/-K111 genotype is associated with CTCL. We found a significant increase in the frequency of detection of the -/-K111 genotype in Caucasian patients with severe CTCL and/or Sezary syndrome (n=35, 37.14%), compared to healthy controls (n=160, 15.6%) [p=0.011]. The -/-K111 genotype was also found to vary in HIV-1 infection. Although Caucasian healthy individuals have a similar frequency of detection of the -/- K111 genotype, Caucasian HIV Long-Term Non-Progressors (LTNPs) and/or elite controllers, have significantly higher detection of the -/-K111 genotype (30.55%; n=36) than patients who rapidly progress to AIDS (8.5%; n=47) [p=0.0097].ConclusionOur data indicate that pericentromeric instability is associated with more severe CTCL and/or Sezary syndrome in Caucasians, and appears to allow T-cells to survive lysis by HIV infection. These findings also provide new understanding of human evolution, as the -/-K111 genotype appears to have arisen out of Africa and is distributed unevenly throughout the world, possibly affecting the severity of HIV in different geographic areas.
Keywords: HERV-K; K111; Pericentromeric instability; Centromeres; CTCL; AIDS; HIV; MYCOSIS-FUNGOIDES; INSERTIONAL POLYMORPHISMS; EUROPEAN-ORGANIZATION; INTERNATIONAL-SOCIETY; CONSENSUS STATEMENT; MOLECULAR-CLONING; TASK-FORCE; NP9; SEQUENCES; REVEALS